Implementation of the CLIO Automated Dispensing System for [¹⁸F] FDG: Enhancing Safety and Operational Efficiency at NINMAS (Bangladesh Journal of Medical Physics, 2025)
The [18F] 2-fluoro-2-deoxyglucose, [18F] FDG is a commonly used PET radiopharmaceutical for imaging in cardiology, neurology, and oncology. Using an 18/9 MeV IBA cyclotron, [18F] FDG is produced at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) and distributed to all PET-CT facilities in Dhaka. Manual dispensing of [18F] FDG, involving repeated handling of high activity vials, was carried out for several batches before the CLIO (Volumetric dispensing system manufactured by COMECER) automated dispensing system was introduced at our institute to enhance efficiency, accuracy, and radiation safety. This study aimed toward evaluating the effectiveness of the CLIO automated dispensing system in [18F] FDG production at NINMAS, with a particular emphasis on workflow quality, operational efficiency, and radiation safety in comparison to manual dispensing. The 18O(p,n)18F nuclear reaction was used to produce [18F] Fluoride, which was synthesized to [18F] FDG using an automated synthesis module (Synthera®). The manual approach involved measuring activity in a Dose Calibrator, diluting it to the necessary concentration, and then using syringes to dispense it into individual vials. In the automated process, CLIO used robotic handling to dispense pre calculated volumes in a shielded hot cell. The exposed radiations were recorded at approximately 30 cm, 1 m, and 2 m away from the dispensing site. TLD badges and pocket dosimeters were used to track individual doses. For both processes, operational metrics such as staffing, documentation, preparation time, dose repeatability, and delivery compliance were noted. The CLIO system reduced average radiation exposure by 80–97% across all measured distances, with the largest reduction at ~30 cm (45.0 ± 2.9 μSv/h to 9.0 ± 0.6 μSv/h). Pocket dosimeter readings decreased by 66.7% (30 μSv/day to 10 μSv/day), while TLD whole-body doses remained same (